EEG and Slit Ventricle Syndrome (SLV) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The EEG changes and the frequency and type of epilepsy in patients with slit ventricles has been analyzed in 113 shunt-treated hydrocephalic children reported from the Department of Pediatrics, University of Oulu, Finland, and the Regional Pediatric Habilitation Center, Gothenburg, Sweden.